Jejak Pemikiran Azyumardi Azra dalam Konteks Islam Melayu: Dari Islamisasi Hingga Pembaruan Pendidikan - Fathatul Khoiriyah; Jossieselfiah; Muhamad Fauzi; Abu Mansur (MODELING: Jurnal Program Studi PGMI, 2025)
This study examines Azyumardi Azra’s thought on the Islamization of the Malay world and its relevance to contemporary Islamic education. The focus of the analysis includes the process of Islamization facilitated through transnational scholarly networks, as well as the application of the concepts of moderation, cosmopolitanism, and the integration of knowledge within educational practice. Employing a qualitative approach through library research, this study analyzes Azra’s works alongside relevant literature on Malay Islamic history, scholarly networks, moderation, and the reform of Islamic education. The findings indicate that the Islamization of the Malay world unfolded dynamically through intellectual exchange and the accommodation of local cultures, ultimately shaping a tradition of Islam that is moderate, inclusive, and cosmopolitan. Azra’s ideas provide a significant foundation for the development of Islamic education curricula that emphasize moral values, tolerance, and global literacy, while simultaneously strengthening a contextualized and culturally grounded Islamic identity